A New Design of Fractal Optical Modulation - Mohammad, A. A .; Harby, K.H.; Al-Aish, T. A. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper it was designed a new fractal optical modulation by using a new iteration of fractal function, the result was analyzed by MTF evaluation, and it compared with results of normal optical modulation.The normal and fractal optical modulator is a circular disc which has a radius R=9cm, both of them consist of twenty sectors, ten sectors are opaque and the other ten sectors are transmitted for the light.      The fractal optical modulator contains two patterns, the pattern two can be used to detect the target, and pattern one can be used to lock the targetThe best similarity of MTF behavior for normal and fractal Reticle was evaluating the power transparent depends on the size of the laser spot and the size of the sector, where the proportionality between them is directly.